Contextual challenges and impacts on the surgical ecosystem in Chiapas, Mexico: A qualitative study - Zachary Fowler; Amina Rahimi; Alejandra Cantu Aldana; Tarsicio Uribe-Leitz; Fernando Carrillo-Villaseñor; Lina Roa; Sarah K. Hill; Valeria Macias; Manuel Castillo-Angeles; Amanda J. Reich (PLoS ONE, 2025)
Chiapas is a state in southern Mexico that faces significant challenges in healthcare delivery. Strengthening the surgical system requires a comprehensive understanding of all health system domains and the contextual factors that influence care delivery. This study used qualitative methods to identify factors related to both gaps and successes in surgical care in Chiapas, Mexico. Semi-structured interviews were conducted with 23 participants at 15 public and private hospitals. Participants consisted of nurses, physicians, surgeons, and hospital administrators. Interviews were transcribed, and a codebook was developed and applied to all interviews. Recurring themes were identified and described using thematic analysis. Four themes characterizing the challenging context through which care is delivered were identified: referral system challenges, workforce shortages, insufficiencies in perioperative and nonoperative care, and waste and mismanagement of resources. Three themes related to innovations and workarounds were identified: efforts to maximize resources and reduce waste, strategies to reduce language barriers, and planning to account for clinical needs in situations of limited access and emergencies. Gaps and challenges within the surgical system of Chiapas lead to challenges in care delivery across all domains of the health system. However, several solutions have emerged among local providers. Insight into these factors can be used in planning efforts to improve access to safe and effective surgical care.